Система направлений и фазовых соотношений электромагнитных величин при численных расчетах магнитных полей в турбогенераторе - Милых, Владимир Иванович; Полякова, Наталия Владимировна; Milykh, V. I.; Polyakova, N. V. (НТУ "ХПИ", 2011)
Представлена система направлений токов в обмотках турбогенератора, которая позволяет получать на основе численных расчетов магнитных полей согласованные фазовые – временные и пространственные соотношения совокупности электромагнитных величин, характеризующих его работу.

The system of directions of currents in the windings of turbogenerator is presented for the numeral calculations of the magnetic fields. It allows to get the coordinated phase – temporal and spatial correlations of aggregate of electromagnetic sizes characterizing the work of turbogenerator
A system of directions and phase relationships for electromagnetic parameters at numerical calculations of magnetic fields in a turbogenerator
Keywords: программа FEMM; магнитное потокосцепление; численные расчеты